Murat Reis complex: Survey, Documentation and Restoration of the Mosque - Chrysidi, Anna; Elena, Konstantinidou; Androniki, Miltiadou - Fezans; Eleftheria, Tsakanika (Technical Annals, 2023)
At the northern end of the new city of Rhodes, just outside the medie- val city an 8-acre "dead zone" includes the cemetery and the "Murat Reis" com- plex. The paper is based on a diploma thesis prepared in the framework of the interdepartmental postgraduate program "Protection of Monuments", of NTUA. The subject of the diploma thesis was the historical and architectural documen- tation, the constructional analysis, the recording of the pathology and the quali- tative interpretation of damages, the elaboration of a proposal for the restoration of the mosque, as well as of a proposal for the integration of the surrounding area of the cemetery into the modern urban landscape and the life of the city. The main findings of a detailed historical and architectural research are first presented, re- garding the historical development of the city and the zoning rearrangements that took place during the Ottoman period in Rhodes. The work focuses on the long- term development of the area where the Murat Reis complex is located, as well as on the documentation and evaluation of its current characteristics. In the next stage, the historical documentation of the mosque is carried out, as well as its architectural and structural survey, including detailed photographic documenta- tion, in order to record and study its main morphological and structural elements. Moreover, an analytical and systematic understanding of the construction details of the various structural and architectural elements of the building, their pathol- ogy, as well as the qualitative diagnosis of the main causes of damage were at- tempted. On this basis, an intervention proposal was drawn up, aiming at the ar- chitectural and structural restoration of the mosque. The restoration proposal was driven by highlighting the history, function and value of the Murat Reis complex as a single entity and transforming the abandoned area into a cultural park of hyperlocal significance.